2004
DOI: 10.1897/03-85
|View full text |Cite
|
Sign up to set email alerts
|

Harbor seals (Phoca vitulina) in British Columbia, Canada, and Washington State, USA, reveal a combination of local and global polychlorinated biphenyl, dioxin, and furan signals

Abstract: The harbor seal (Phoca vitulina) can serve as a useful indicator of food web contamination by persistent organic pollutants (POPs) because of its high trophic level, wide distribution in temperate coastal waters of the Northern Hemisphere, and relative ease of capture. In 1996 through 1997, we live-captured 60 harbor seal pups from three regions, spanning remote (Queen Charlotte Strait, BC, Canada), moderately industrialized (Strait of Georgia, BC, Canada), and heavily industrialized (Puget Sound, WA, USA) mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 46 publications
8
116
3
Order By: Relevance
“…Burse et al (1994) reported 1.33 ppm PCBs in a composite of four samples of bluefish from Clarks Cove and 0.42 ppm PCBs in a composite of three bluefish purchased in a seafood market in South Dartmouth, Massachusetts. High levels of PCBs, similar to those found in YOY bluefish from the New Bedford Harbor, have been reported in only a limited number of marine species like the blubber biopsies of bottlenose dolphins , harbor seals (Ross et al, 2004) and the Pacific orcas (Ross et al, 2000).…”
Section: Pcb Contamination Of Yoy Bluefishmentioning
confidence: 52%
“…Burse et al (1994) reported 1.33 ppm PCBs in a composite of four samples of bluefish from Clarks Cove and 0.42 ppm PCBs in a composite of three bluefish purchased in a seafood market in South Dartmouth, Massachusetts. High levels of PCBs, similar to those found in YOY bluefish from the New Bedford Harbor, have been reported in only a limited number of marine species like the blubber biopsies of bottlenose dolphins , harbor seals (Ross et al, 2004) and the Pacific orcas (Ross et al, 2000).…”
Section: Pcb Contamination Of Yoy Bluefishmentioning
confidence: 52%
“…Dose response relationships for many of the congeners have not been well established [9]. The highest PCB values reported within marine mammals was 18,135 µg/kg within Puget Sound harbor seal (Phoca vitulina) blubber [10]. Of the cetaceans, transient Kenai Fjords/Prince William Sound killer whale blubber had the highest value of 230,000 ng/g [5].…”
Section: Dichlorodiphenyltrichloroethane (Ddt)mentioning
confidence: 99%
“…Knowledge of food web dynamics allows managers to monitor movement of contaminants in the ecosystem (Ross et al 2004) and the effects of the toxins on species composition, abundance, diversity, and ultimately, the food web itself. Bioaccumulation of toxins has been shown to impact multiple species in many ways, from the immunologic health of harbor seals (Ross et al 1996) to the density and species richness of Phoxocephalid amphipods (Swartz et al 1982).…”
Section: Understand the Food Webmentioning
confidence: 99%